2020
DOI: 10.17221/230/2020-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold and warm white light on selected endocrine and immune parameters of broiler embryos and hatchlings

Abstract: Lighting conditions during incubation can influence embryonic development, post-hatching ontogeny and production efficiency. Previous studies revealed that different light colours differently affect pineal melatonin biosynthesis in embryos and postembryonic development of broiler chickens, but physiological mechanisms mediating these effects are not known. Cold and warm white light consists of different wavelengths and therefore the aim of the present study was to explore if these two lights can differently in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Incubation under blue light resulted in the lowest melatonin biosynthesis. In another study (Drozdova et al 2020), we showed that incubation in warm and cold white light did not significantly influence embryonic melatonin biosynthesis, and therefore, it is possible that distinct wavelengths may selectively influence postembryonic development and behaviour.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Incubation under blue light resulted in the lowest melatonin biosynthesis. In another study (Drozdova et al 2020), we showed that incubation in warm and cold white light did not significantly influence embryonic melatonin biosynthesis, and therefore, it is possible that distinct wavelengths may selectively influence postembryonic development and behaviour.…”
mentioning
confidence: 82%
“…In plasma, we measured glucose, cholesterol and triacylglycerol concentrations using commercially available kits according to the manufacturer's instructions (Erba Lachema s.r.o., Brno, Czech Republic). Plasma levels of the thyroid hormones triiodothyronine (T 3 ) and thyroxine (T 4 ) (Institute of Isotopes Co., Ltd., Budapest, Hungary), as well as the stress hormone corticosterone (DRG Instruments GmbH, Marburg, Germany) were determined by commercial radioimmunoassay kits according to the manufacturer's instructions (Drozdova et al 2020). Hormones were https://doi.org/10.17221/80/2021-CJAS light treatment and age, using the Holm-Sidak post hoc test.…”
Section: Methodsmentioning
confidence: 99%
“…The cool white LED (5,000 K) containing more blue wavelength could improve weight gain and reduce stress and fear responses of broilers as compared to warm white LED (2,700 K) (Archer, 2018). However, it was shown that incubation in warm and cold white light did not significantly influence embryonic melatonin biosynthesis in the pineal, T 3 , T 4 , corticosterone hormone levels in the blood and immune system-related genes, presenilin-1, and avian betadefensin1, in the duodenum and bursa Fabricius (Drozdova et al, 2020). The authors concluded that selective effects of distinct wavelengths on embryonic and post-embryonic development might be more profound than the effects of change in the color temperature of polychromatic light.…”
Section: Effects Of Light On Embryo Development and Post-hatching Growthmentioning
confidence: 96%
“…A stronger humoral immune response to keyhole limpet hemocyanin (KLH), which is a non-pathogenic protein antigen and often used to assess humoral immunity, was reported in broilers compared to dark incubation when eggs were exposed to a 12L:12D white fluorescent light (Archer and Mench, 2013). Drozdova et al (2020) further investigated if the color temperature of white light affects the immune system and did not find any significant effect on the expression of genes involved in innate immune responses in the duodenum and bursa of Fabricius. However, distinct effects of different wavelengths have been reported.…”
Section: Effects Of Light On Embryo Development and Post-hatching Growthmentioning
confidence: 99%